Improving Student Well-being in School - Farah Aulia (Fakultas Ilmu Pendidikan)
Schools have an important role in supporting student well-being as microsystems that affect student development, social contexts where students interact and influence each other with teachers, peers and staff as well as schools as a community. Student well-being is related to a number of important factors including academic achievement, physical and mental health, satisfying interpersonal relations and success at work. This article examines the role of schools in efforts to improve student well-being.A whole-school approach that involves all the components in a school is needed to support student well-being.